Prevalence and determinants of early childhood caries among preschool children in district Shimla, North India: a cross -sectional study - Seema Thakur; Reetica Sharma; Parul Singhal; Deepak Chauhan (BMC Oral Health)
Abstract Background A high prevalence of early childhood caries (ECC) has been reported in children over the past few decades making it a major health burden. The study investigated the prevalence of ECC and associated factors among the preschool children of Shimla district. Methods An observational cross-sectional study was carried out in various government and private preschools of district Shimla from July 2022 to November 2022 where children in the age group of 3–5 years were screened for ECC using the dmft index and their BMI (body mass index) and salivary pH was recorded. Information regarding socio-economic status (SES), feeding, dietary and oral hygiene habits were collected through questionnaire circulated to the parents. Prevalence of ECC was calculated. Association of various factors with ECC prevalence was done using chi square test and correlation of factors with prevalence of ECC was assessed using Spearman’s correlation coefficient. Binomial logistic regression analysis was performed to assess these variables for prevalence of ECC. The level of statistical significance was determined at p ≤ 0.05. Results 1224 school children and their parents were included in the study. The overall prevalence and mean dmf score was 61.6% and 3.21 ± 3.92 respectively. Among these 57% children had caries at 3 years, 64.7% at 4 years and 69.5% at 5 years. Increasing age was associated with increasing prevalence of ECC (OR = 1.034, p = 0.006). The upper socio economic status was significantly associated with risk of ECC than other categories (p = 0.046). Decreasing salivary pH was associated with increased prevalence of ECC (OR = 0.656, p <. 001). Conclusion The study demonstrated a high prevalence of ECC in the district along with setting the baseline data for the region. Increasing age, upper socioeconomic status and decreasing salivary pH are significantly associated in likelihood of caries whereas other factors like BMI, dietary and feeding and oral hygiene habits are also important factors which were directly or indirectly related to the burden of this disease. Efforts should be made to create more awareness and provide oral health care facilities to help keep the disease under control.